Motion characteristics of Under-15, Under-17 and Under-19 Italian youth women soccer matches - Mordillo, E.; Zago, M. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: Despite the constant development of women`s football, few studies to date addressed the physical requirements of youth female soccer players in regional (specific) contexts. This research characterized the activity profiles of élite Italian U15, U17 and U19 female games. METHODS: Sixty players (U15, N.=18; U17, N.=20; U19, N.=22) from a high-level club in North-East Italy were involved. Players were equipped with a 10-Hz GPS device. Forty-six games were monitored (9 vs. 9 for U15, 11 vs. 11 for U17-U19) and the following dependent variables were extracted: total distance, equivalent distance, normalized distance (m/min) in six speed and metabolic power ranges. Total high-speed (>14.1 km/h) and total high-power (>18 W) distances were computed based on thresholds parametrized to the young female athlete. A multivariate general linear model was fit to analyze the effect of age category, match periods and their interaction. RESULTS: Some game parameters increased with age, especially from U15 to U17. Among them: total distance (5.5 km, 7.8 km, and 8.8 km for U15, U17, U19), distance at very-high (18-22 km/h) and maximum (>22 km/h) speed, distance at high power (18-31.5 W). Normalized distance was ~90 m/min and comparable among age groups. A reduction of very-high (31.5-49.5 W) and maximum power (>49.5 W) distance was observed in U15 matches, and of high-power distance in U17 and U19. CONCLUSIONS: These findings quantify the physical demands of Italian youth female match-play. These data support evidence-based training planning, set a reference for players approaching higher playing standards, and could suggest informed redesign of playing formats.